Clima laboral en el Cuerpo de Bomberos Municipal del cantón Puebloviejo - Ortega Villamar, Laleska Leonor (2021)
The work environment is a concept with a long tradition in studies and research on the human factor in companies and organizations, it is used in order to determine the internal labor relationship, so that staff can get involved with the organizational objectives. The causes of all productivity involve the human element and therefore its behavior, which leads to studying its qualities, conditions and effect; Therefore, it is important to attend to these elements, offering a comfortable environment to guarantee lasting success in the institution, whether public or private, this factor can be positive or negative, which is established by a series of aspects related to the attitudes of each one of the members of the institution The present investigative work was carried out in order to identify and analyze the factors that affect the work environment within the Municipal Fire Department of the Canton Puebloviejo, based on the attitudes, motivation, empowerment, safety and behavior of the collaborators, taking into account that They are essential within the organization to improve performance, performance and work environment.